A Study of Somatic Auditory Visual Intellectual-Based Learning Videos to Improve Learning Achievement in Writing English Procedural Texts - Hanifah Fardhany, Cut; Herpratiwi, Herpratiwi; Sukirlan, Muhammad (UNDIKMA, 2024)
Learning is essentially an effort to make students learn so as to gain knowledge and knowledge, mastery of skills, as well as attitude formation and attitude change. Mastery of English is a means to boost human resources. Global competition in all fields demands an increase in the quality of human resources (HR). This study aims to improve the decline in learning achievement in writing English-based procedure texts by using SAVI learning videos. This research method is a literature review with 10 articles published from 2017 to 2023. Overall, somatic auditory visual intellectual-based learning video is an effective approach in improving learning achievement in writing English procedure text. This approach provides opportunities for learners to be actively involved, uses various learning modalities, and stimulates emotional engagement, thus improving their understanding and writing skills.